The Social Function of 4 Ezra - Esler, Philip Francis (Journal for the study of the New Testament, 1994)
Hitherto an air of pessimism has often attended enquiry into the social context and function of 4 Ezra. The aim of this article is to propose a particular social function for the text. The methodology employed uses social-scientific ideas and perspectives, especially those dealing with introversionist religious responses generated by defeatd indigenous cultures, together with a literary analysis utilizing Russian formalist theory. It is argued that the text, especially in the response of the seer to the vision of the mourning woman who is transformed into a city, provides a means for Israel to reduce extreme dissonance occasioned by the sack of Jerusalem in 70 CE and its aftermath. It is further argued that the emphases on law and eschatology in the text are not aspects of an interest in individualistic works-righteousness, but are rather directed to the need for Israel to rediscover its corporate identity and to gather around the Law in a manner akin to other groups who replace frustrated millennial dreams with the quiet fulfillment of ethical obligations.